Influence of variable concentration of ethanol intake on alveolar bone loos in rats periodontitis model - De Souza, Daniela Martins [UNESP]; Da Rocha, Rosilene Fernandes [UNESP] (My University, 2014)
Objective: The aim of this study was to morphometrically evaluate the effect of variable concentration of ethanol consumption on alveolar bone loss associated with ligature-induce periodontitis in rats. Methods: Thirty-six male rats (Wistar, 120 days-old) were randomly divided into four groups of nine animals each. The rats received daily rat chow and administration of water free liquid diet (control), 10% alcohol diet (10% ethanol), 20% alcohol diet (20% ethanol) or 30% alcohol diet (30% ethanol). After anesthesia, cotton ligatures were placed around the cervix of the right upper second molar, leaving the contralateral teeth unligated. After 8 weeks, the rats were sacrificed and the maxillary bones were removed and alveolar bone loss was analyzed by measuring the distance between the cementoenamel junction and the alveolar bone crest at the buccal site of the right upper second molar. Results: Unligated groups showed no significant differences between each other (p>0.05). In ligated groups, rats receiving 10%, 20% and 30% ethanol showed significantly greater bone loss compared to control rats. Conclusion: These results demonstrate that variable concentration of ethanol consumption may increase alveolar bone loss in male rats, independent of dose used, associated with ligature-induce periodontitis in rats.
Keywords: Alveolar bone loss; Ethanol; Periodontitis; Rats